Contribution of quality thinking to the operations design: gap finding and addressing - Bravo, A.; Silva, J.; Pereira, Z. (Managing operations in service economies, XVII international annual conference of the EurOMA, 2010)
This exploratory exercise argued for the quality management importance in organizational performance. A sample of quality thinking showed TQM as its acceptable representative. Moreover, TQM was found linked to several management issues close to business competitiveness, despite reports about its unsuccessful implementation. Thus, a framework to accommodate the development of an audit tool to find out the missing links of TQM implementation in operations design was proposed. A qualitative case study strategy in the pharmaceutical industry, following a Soft Systems approach was also suggested.